About Sculpture. (London : Anthony d'Offay Gallery, 1988)
Andre, Carl ; Beuys, Joseph ; Gilbert & George ; de Kooning, Willem ; Kounellis, Jannis ; Long, Richard ; Merz, Mario ; Nauman, Bruce ; Smith, David ; Twombly, Cy ; Webb, Boyd ; Weiner, Lawrence
Engels
About Sculpture, Anthony d'Offay Gallery, London, 28.01. - 05.03.1987
boek